HYDROCARBON POTENTIAL OF THE OFFSHORE AKIMEUGAH BASIN FROM MESOZOIC-PALEOZOIC BASED ON GEOLOGICAL AND GEOPHYSICAL ANALYSIS - Setiadi, Imam; Rasyid, Faris N; Zulivandama, Shaska Ramadhan; Firdaus, Yulinar; Santy, Lauty D.; Saleh, Hanif M.; Rachman, Muhammad G.; Djaja, Andrian W.; Nurdin, Nazar; Rahardiawan, Riza; Subarsyah, Subarsyah (BULLETIN OF THE MARINE GEOLOGY, 2025)
Akimeugah Basin is one of the basins with discovery status, however hydrocarbon production has not yet been established. One of potential petroleum play type for further investigation, estimated to contain hydrocarbon reserves in the offshore Akimeugah Basin, is the Mesozoic–Paleozoic sedimentary play, interpreted to have originated from the Australian passive margin. This study aims to analyze geological and geophysical data to delineate the sub-basin pattern and characterize petroleum system elements. The analysis integrates gravity data interpretation, geochemical evaluation of source rocks, and subsurface interpretation based on seismic and well data. Results indicate that source rocks in the Kola-1 well are primarily composed of Type III (gas-prone) and secondarily of Type II (oil/gas-prone) kerogen. Thermal maturity analysis shows that the Woniwogi, Aiduna, and Modio Formations have reached the oil window. Reservoir potential has been identified in the Tipuma Formation (Triassic), Aiduna Formation (Permian), and Modio Dolomite (Devonian–Silurian). Seal rocks consist of regional and intraformational units composed of tight siltstone and shale. Trapping mechanisms in this area include a combination of structural traps such as fault-bounded anticlines and stratigraphic traps represented by sub-unconformities. Identified exploration leads include seven within the Modio Dolomite structural play, six within the Permian Aiduna Sandstone play, and four within the Triassic Tipuma Sandstone play.